(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
A methodological approach for the physiological support of climbing teams preparing for ascent, based on the analysis of the literature and our own research, which includes a course of intermittent hypoxic hypobaric training in the conditions of the hypobaric chamber, is proposed. The course of hypoxic training of climbers is proposed to be carried out under conditions of modeling heights of less than 3000 m above sea level, at least 10 ascents lasting 1 hour daily, with pulse oximetry monitoring. In order to control the physical performance and endurance of climbers, it is recommended to perform a cardiorespiratory test on a bicycle ergometer before and after training with an assessment of the maximum power of muscle work, the value of maximum oxygen consumption at peak exercise and the anaerobic threshold. This approach was tested with the participation of a team of 8 climbers (6 men, 2 women) with different ages and levels of training. The comparison of the final indicators of cardiorespiratory tests with the initial ones showed that all climbers retained physical performance and endurance after completing the course of hypoxic training.